Training in reviewing: a teaching exercise on editions of contemporary texts (Prassi Ecdotiche della Modernità Letteraria, 2025)
This contribution offers a reflection on the relevance of editorial philology methods within the field of contemporary Italian literary studies. Drawing on recent teaching experience in a graduate course in Publishing, the essay illustrates how the design and use of a structured review form can serve as an educational tool for the analysis of critical and scholarly editions of modern and contemporary texts. The paper highlights the challenges of integrating philological awareness into contemporary literary criticism and proposes the structured review as a valuable exercise for developing skills in examining the mechanisms of textual transmission and editorial criteria.
Keywords: Editorial philology; Contemporary Italian literature; Critical edition; Scholarly edition; Teaching philology; Editorial practices